“Compound Dispossession” in Southern Ontario: Converging Trajectories of Colonial Dispossession and Inter-Indigenous Conflict, 1886–1900 - Reid, Darren (University of Toronto Press Inc. (UTPress), 2022)
Throughout the 1880s and 1890s, two First Nations groups—the Chippewa of the Thames and the Six Nations of the Grand River—attempted to evict two other First Nations groups—the Munsee of the Thames and the Mississauga of the Credit—from the Thames and Grand River reserves in southern Ontario. These land disputes were successfully resolved by the turn of the twentieth century and no evictions did take place, but the 20 years of conflict are revealing of the complexities, contingencies, and evolutions of dispossession in Canada over the nineteenth century. This article presents a narrative of these attempted evictions and proposes the concept of “compound dispossession” as a means of grappling with these complexities. It is argued that compound dispossession not only captures the snowballing complications of historical dispossessions over time, but also captures the imbrication of multiple disparate trajectories of dispossession as the pressures of settler land hunger and encroachments on Indigenous sovereignty in the late nineteenth century bore down on four neighbouring First Nations groups simultaneously. Rather than interpreting these conflicts through a binary of assimilation/resistance, compound dispossession suggests the pervasiveness of dispossession as a discourse and the agency of dispossession as an adaptation to the unfolding settler-colonial paradigm.